2017
DOI: 10.2147/ppa.s144624
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence and disease burden of individuals with rheumatic diseases admitted as outpatients to a large rheumatology center in Shanghai, China

G lu2,
et al.

Abstract: PurposeThe purpose of this study was to determine treatment adherence and disease burden, analyze detailed medication problems experienced by patients, and identify factors associated with adherence in patients with rheumatic diseases in China.Patients and methodsPatients with confirmed diagnoses of ankylosing spondylitis (AS), rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE) were recruited, regardless of demographics, disease severity, and treatment characteristics. Adherence was assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 38 publications
5
24
2
Order By: Relevance
“…AE adverse event, csDMARD conventional synthetic disease-modifying antirheumatic drugs, HCQ hydroxychloroquine, LEF leflunomide, MTX methotrexate, SASP salazosulfapyridine a Rheumatologists were asked to estimate whether each AE was common, and calculated the number and proportion of people who believed it was a common AE b Patients were asked to report the AEs they once experienced and calculated the number and proportion of each AE However, due to the paucity in the literature of similarly designed studies, AE occurrence cannot be directly compared. The non-compliance rate (40.8%) was within the range of those reported by other RA studies conducted in China (19.8-61.4%) [18,19]. Non-compliance would eventually worsen disease activity, which acts against the treat-to-target strategy.…”
Section: Discussionsupporting
confidence: 67%
“…AE adverse event, csDMARD conventional synthetic disease-modifying antirheumatic drugs, HCQ hydroxychloroquine, LEF leflunomide, MTX methotrexate, SASP salazosulfapyridine a Rheumatologists were asked to estimate whether each AE was common, and calculated the number and proportion of people who believed it was a common AE b Patients were asked to report the AEs they once experienced and calculated the number and proportion of each AE However, due to the paucity in the literature of similarly designed studies, AE occurrence cannot be directly compared. The non-compliance rate (40.8%) was within the range of those reported by other RA studies conducted in China (19.8-61.4%) [18,19]. Non-compliance would eventually worsen disease activity, which acts against the treat-to-target strategy.…”
Section: Discussionsupporting
confidence: 67%
“…38 On the other hand, the classic triple therapy of MTX+SSZ+HCQ, which bore abundant evidence in terms of efficacy; 8 , 17 however, its compliance was problematic in Chinese patients according to our previous real-world data. 14 The main reason seemed to be that patients were reluctant to take an extra 4–8 SSZ tablets each day (with a therapeutic dose of 1–2 gram/day). MTX+LEF apparently provided an alternative option; and within the dose range the safety profile was good.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Previous studies demonstrated that the global disease burden of RA ranked fifth in musculoskeletal diseases, and its average annual direct cost in China could reach $3,069. 14,15 The increasing disease burden in light of pharmacoeconomic analysis is at least partially relevant to the emerging targeted therapies. Therefore, in the real-world practice, to give the csDMARDs a "second chance" is always a serious consideration for both health providers and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of patients with SLE, which had different populations and methodologies, reported that adherence ranged from 3 to 76%, 67% for glucocorticoids, 48.6%~ 93% for hydroxychloroquine, and 57% for other immunosuppressants [46]. Besides, the rate of treatment adherence in China was about 48.7% based on our previous study [7]. Moreover, chronic rheumatic conditions are inclined to result in substantial burdens such as economic burden for patients and their families.…”
Section: Introductionmentioning
confidence: 91%
“…In Europe, the per capita annual direct medical cost of patients with SLE reaches €4748 (US$5037.15), up to US$6269 [810] in the US. Surprisingly, the cost in our previous study of SLE population also reached $5103 in China [7], which is a huge expenditure for a developing country. The results of our previous study suggest that we have defects in the management of lupus patients, and we should take measures to improve their adherence and reduce the disease burden.…”
Section: Introductionmentioning
confidence: 92%